Plasma protein-binding and CSF concentrations of valproic acid in man following acute oral dosing. - Rapeport, W G (1983)
Simultaneous cerebrospinal fluid (CSF), total and free plasma valproic acid (VPA) concentrations were measured in 17 patients receiving two weight-adjusted VPA doses as seizure prophylaxis prior to diagnostic myelography or cisternography. Free drug concentrations were similar when measured by equilibrium dialysis (ED) at 37 degrees C for 24 h (Dianorm) or by a novel ultrafiltration (UF) method (EMIT freelevel system 1, SYVA) (ED:2.3-35.5 mg-1; UF:1.3-33.6 mg-1; r = 0.78, P less than 0.002). There was wide variation in total VPA concentration (39-154 mg-1) and in free fraction (ED: 3.3-25.6%; UF: 5.9-24%). Concentration dependent protein binding was not demonstrated. CSF VPA varied between 4.2 and 25.6 mg-1 and was accurately reflected by free plasma VPA concentrations (ED: r = 0.75, P less than 0.005: UF: r = 0.93, P less than 0.001). CSF concentration also correlated with the total plasma VPA (r = 0.76, P less than 0.005). The Emit freelevel system 1 provides a rapid measure of unbound VPA in the plasma which may be suitable for routine clinical use.